Patients’ Perspectives on Psychiatric Pharmacogenetic Testing - Liko, Ina; Lai, Erika; Griffin, Rachel J.; Aquilante, Christina L.; Lee, Yee Ming (Pharmacopsychiatry, 2020)
Introduction There is growing interest to adopt pharmacogenetic (PGx) testing in psychiatric medicine, despite mixed views regarding its clinical utility. Nevertheless, providers are utilizing PGx testing among patients with mental health disorders. This study sought to assess genotyped patients’ perspectives and experiences with psychiatric PGx testing.Methods Individual semi-structured interviews were conducted among patients with depression who had undergone psychiatric PGx testing. The audio-recorded interviews were transcribed and analyzed inductively and deductively for salient themes.Results Twenty patients (100% Caucasian, 60% female, mean age 39±18 years) were interviewed. The majority of the PGx tests were provider-initiated for patients who failed multiple pharmacotherapies (50%) and/or had medication intolerances (45%). Patients’ pre-testing expectations ranged from hopefulness to indifference to skepticism. Their post-testing experiences varied from optimism to disappointment, with the perceived value of the test influenced by the results and cost of the test.Discussion Genotyped patients had mixed perspectives, expectations, and experiences with psychiatric PGx testing. Their perceived value of the test was influenced by the test outcomes and its cost.
Keywords: Pharmacogenetics; Pharmacogenomics; Patient; Psychiatry